An infrared-radio simulation of the extragalactic sky: from the Square Kilometer Array to Herschel - Wilman, R; Jarvis, M; Mauch, T; Rawlings, S; Hickey, S (2010)
To exploit synergies between the Herschel Space Observatory and next generation radio facilities, we have extended the semi-empirical extragalactic radio continuum simulation of Wilman et al. (2008) to the mid- and far-infrared. Here we describe the assignment of infrared spectral energy distributions (SEDs) to the star-forming galaxies and active galactic nuclei, using Spitzer 24, 70 and 160 micron and SCUBA 850 micron survey results as the main constraints. Star-forming galaxies dominate the source counts, and a model in which their far-infrared-radio correlation and infrared SED assignment procedure are invariant with redshift underpredicts the observed 24 and 70 micron source counts. The 70 micron deficit can be eliminated if the star-forming galaxies undergo stronger luminosity evolution than originally assumed for the radio simulation, a requirement which may be partially ascribed to known non-linearity in the far-infrared--radio correlation at low luminosity if it evolves with redshift. At 24 micron, the shortfall is reduced if the star-forming galaxies develop SEDs with cooler dust and correspondingly stronger Polycyclic Aromatic Hydrocarbon (PAH) emission features with increasing redshift at a given far-infrared luminosity, but this trend may reverse at z>1 in order not to overproduce the sub-mm source counts. The resulting model compares favourably with recent BLAST results and we have extended the simulation database to aid the interpretation of Herschel surveys. Such comparisons may also facilitate further model refinement and revised predictions for the SKA and its precursors.